Tetrahydrobiopterin prevents chronic ischemia-related lower urinary tract dysfunction through the maintenance of nitric oxide bioavailability - Akaihata, Hidenori (Sci Rep, 2020)
This study aimed to investigate the influence of chronic ischemia on nitric oxide biosynthesis in the bladder and the effect of administering tetrahydrobiopterin (BH4), a cofactor for endothelial nitric oxide synthase (eNOS), on chronic ischemia-related lower urinary tract dysfunction (LUTD). This study divided male Sprague–Dawley rats into Control, chronic bladder ischemia (CBI) and CBI with oral BH4 supplementation (CBI/BH4) groups. In the CBI group, bladder capacity and bladder muscle strip contractility were significantly lower, and arterial wall was significantly thicker than in Controls. Significant improvements were seen in bladder capacity, muscle strip contractility and arterial wall thickening in the CBI/BH4 group as compared with the CBI group. Western blot analysis of bladder showed expressions of eNOS (p = 0.043), HIF-1α (p < 0.01) and dihydrofolate reductase (DHFR) (p < 0.01), which could regenerate BH4, were significantly higher in the CBI group than in Controls. In the CBI/BH4 group, HIF-1α (p = 0.012) and DHFR expressions (p = 0.018) were significantly decreased compared with the CBI group. Our results suggest that chronic ischemia increases eNOS and DHFR in the bladder to prevent atherosclerosis progression. However, DHFR could not synthesize sufficient BH4 relative to the increased eNOS, resulting in LUTD. BH4 supplementation protects lower urinary tract function by promoting eNOS activity.